Baicalein ameliorates cognitive decline induced by chronic cerebral hypoperfusion through the SIRT1-mediated Notch1 pathway to improve angiogenesis and suppress neuroinflammation - Li, Meixi; Song, Jiaxi; Niu, Xiaoli; Mo, Feng; Xie, Xiaohua; Li, Xiuqin; Yin, Yu; Wang, Tianjun; Song, Xiujuan; Liu, Jingze; Lv, Peiyuan (Frontiers in Aging Neuroscience, 2025)
IntroductionThe potential for therapeutic strategies that promote angiogenesis and suppress neuroinflammation to ameliorate cognitive decline induced by chronic cerebral hypoperfusion (CCH) has led to their recognition as promising therapeutic targets for vascular dementia (VD). The SIRT1-mediated Notch1 signaling pathway is important in regulating angiogenesis and neuroinflammation. Previous studies have demonstrated that baicalein alleviates cognitive decline in rats with CCH. Nevertheless, it remains unclear whether baicalein can stimulate angiogenesis in the context of VD and whether this cognitive protective effect is achieved by regulating the SIRT1-mediated Notch1 pathway. The aim of this study was to investigate the impact and the underlying mechanism of baicalein on angiogenesis and neuroinflammation in rats with CCH.MethodsAdult Sprague-Dawley (SD) rats were administered baicalein or a SIRT1 inhibitor. Cognitive function was assessed by the Morris water maze (MWM) test, and angiogenesis was assessed by immunohistochemical analysis of microvascular density (MVD) and the number of CD31+/5-bromo-2’-deoxyuridine (BrdU)+ cells. Neuroinflammation and apoptosis were assessed by immunohistochemistry for GFAP, Iba-1, NEUN/cleaved caspase-3, and ELISA analysis for TNF-α and IL-1β. Additionally, Western blotting was employed to evaluate the expression of the SIRT1-mediated Notch1 pathway.ResultsThe results demonstrated that baicalein ameliorated memory and learning deficits in rats following CCH by promoting angiogenesis and suppressing neuroinflammation. However, this protective effect could be reversed by inhibiting SIRT1. Baicalein was observed to up-regulate the expression of SIRT1 and down-regulate the Notch1-related molecules.DiscussionThe SIRT1-related pathway plays a crucial role in regulating angiogenesis and neuroinflammation. Moreover, baicalein exerts a neuroprotective effect against cognitive decline through the SIRT1-mediated Notch1 pathway, which in turn improves angiogenesis and suppresses neuroinflammation.